Maintenance of water tank at Apartment Laguna Biru / Muhammad Azwan Mohtar - Mohtar, Muhammad Azwan (2017)
Practical Training (BSR 360) is the main core subject for the Final Year Student of Diploma in Building Surveying, in UiTM Perak. This course was consisting of 8.0 credit hours, semester 6. Practical Training refers to work experience that is relevant to professional development prior to graduation. One of the requirements for the students of Diploma in Building Surveying to complete the program is the students must complete at least 14 weeks of Practical Training. The purpose of the report is to add the knowledge about the maintenance water tank for water supply. This report describe the method of the maintenance of water tank include the component of water tank.